Predictive Factors for Prostatic Involvement by Transitional Cell Carcinoma of the Bladder - Tabibi, Ali; Simforoosh, Nasser; Parvin, Mahmoud; Abdi, Hamidreza; Javaherforooshzadeh, Ahmad; Farrokhi, Farhat; Soltani, Mohammad Hossein (Urology Journal, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE FA <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} --> <!--[endif] --> Purpose: To evaluate the predictive factors for prostatic involvement according to the bladder transitional cell carcinoma (TCC) characteristics in a prospective study. Materials and Methods: Hundred patients with the bladder TCC who had undergone standard radical cystoprostatectomy were enrolled in this study. A number of factors, including vascular and perineural invasion, number of tumors, maximum diameter of the tumor, presence of carcinoma in situ, distance between the tumor and the bladder neck, grade, and local stage of the tumor were recorded, and their elationships with prostatic involvement were studied. In addition, hydronephrosis and age of the patients were included in the analysis. Results: The mean age of the patients was 62.6 ± 10.8 years. Of a total of 100 patients, 21 were found to have prostatic involvement with TCC. Univariate statistical analysis showed that vascular invasion and the distance between the tumor and the bladder neck were significantly related to the prostatic involvement (P = .001 and P < .001) and tumor stage had relatively low P value (P = .08). In the logistic regression, only the distance between the tumor and the bladder neck was found to be significantly related to the prostatic involvement (P = .004). Conclusion: This study demonstrated that distance between the tumor and the bladder neck is a predictive factor for prostatic involvement; hence, prostate-sparing or capsule-sparing cystectomy in patients with tumors in short distances from prostatovesical junction is not rationale and should be avoided.